2017
DOI: 10.1371/journal.pmed.1002195
|View full text |Cite
|
Sign up to set email alerts
|

Artificially Sweetened Beverages and the Response to the Global Obesity Crisis

Abstract: Christopher Millett and colleagues argue that artificially sweetened beverages should not be promoted as part of a healthy diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 57 publications
3
60
0
2
Order By: Relevance
“…A recently published study from 10 European countries found a positive association between both sugar-sweetened (1-2/day and > 2/day) and artificially sweetened beverages (> 2/day) and all-cause mortality when compared to referent category (< 1/month). This study used data on 451,743 participants over a mean follow-up of 16.4 years [25]. Another study used Model 0: unadjusted Model 1: adjusted for sex, age and ethnicity Model 2: model 1 also adjusted for income, highest qualification, physical activity, sedentary behaviour, total energy intake, body mass index, smoking status and alcohol intake Model 3: model 2 also adjusted for total sugar intake and total fat intake (total sugar intake was not included in the analysis of sugar-sweetened beverages) Model 4: model 3 also adjusted for fresh fruit intake, vegetable intake, total fibre intake, red meat intake and processed meat intake N number, HR hazard ratio, CI confidence interval data from two US cohorts-the Nurses' Health Study (NHS) of 80, 647 women and the Health Professionals Follow-up Study (HPFS) of 37,716 men [3]-and looked at the intake of sugar-sweetened and artificially sweetened beverages and all-cause mortality and mortality from cancers and cardiovascular causes over a follow-up of 34 and 28 years, respectively.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…A recently published study from 10 European countries found a positive association between both sugar-sweetened (1-2/day and > 2/day) and artificially sweetened beverages (> 2/day) and all-cause mortality when compared to referent category (< 1/month). This study used data on 451,743 participants over a mean follow-up of 16.4 years [25]. Another study used Model 0: unadjusted Model 1: adjusted for sex, age and ethnicity Model 2: model 1 also adjusted for income, highest qualification, physical activity, sedentary behaviour, total energy intake, body mass index, smoking status and alcohol intake Model 3: model 2 also adjusted for total sugar intake and total fat intake (total sugar intake was not included in the analysis of sugar-sweetened beverages) Model 4: model 3 also adjusted for fresh fruit intake, vegetable intake, total fibre intake, red meat intake and processed meat intake N number, HR hazard ratio, CI confidence interval data from two US cohorts-the Nurses' Health Study (NHS) of 80, 647 women and the Health Professionals Follow-up Study (HPFS) of 37,716 men [3]-and looked at the intake of sugar-sweetened and artificially sweetened beverages and all-cause mortality and mortality from cancers and cardiovascular causes over a follow-up of 34 and 28 years, respectively.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Contemporary obesity policies have focused on sugar, but there has been less consideration of ASBs , or overall sweetness (added sugars and artificial sweeteners) in children's diets . Recent research has shown that a sizeable proportion of drinks marketed to children contains artificial sweeteners and that ASB consumption may be associated with higher sugar intake from solids for boys .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from the USA indicates increased purchases of food and beverages containing artificial sweeteners, or those containing both artificial and added sugars (9). Thus, the relative importance of ASBs in the global food system may be increasing, indicating the imperative for increased research and policy attention on these products (10).…”
Section: Discussionmentioning
confidence: 99%
“…Well‐formulated sugar taxes are applied to imports and exports equally, to ensure all goods are targeted. In addition, many also target artificial sweeteners because there is some evidence that the use of artificial sweeteners increases the desire for sweet‐tasting products and no resultant decrease in caloric intake occurs . Studies in the USA showed that consumption of zero‐sugar soft drinks correlated just as strongly with rates of obesity as sugary goods did although the reasons for this effect remain unclear …”
Section: The Pros and Cons Of A Tax On Ssbsmentioning
confidence: 99%